High-dose cytarabine monotherapy is superior to standard-dose cytarabine- based multiagent sequential treatment cycle for consolidation treatment in adult (14-59 years) AML patients according to European Leukemia Net 2022 risk stratification - Wang, Xiaoyu; Liu, Dan; Chen, Erling; Wang, Li; Zhao, Na; Zhou, Li; Tong, Juan; Xue, Lei; Zhang, Lei; Geng, Liangquan; Tang, Baolin; Liu, Huilan; et al. (Frontiers in Oncology, 2023)
We firstly investigate based on 2022 European Leukemia Net (ELN) risk stratification, whether standard-dose cytarabine based multiagent sequential chemotherapy (SDMSC) is more beneficial than high-dose cytarabine (HDAC) monotherapy in consolidation for the survival of adult acute myeloid leukemia (AML) patients. One hundred and eighty-three AML patients with complete remission (CR) were evaluated. The 3-year relapse rate was 33.4% in the HDAC group and 50.5% in the SDMSC group (p=0.066). The 3-year overall survival (OS) and event-free survival (EFS) rates in the HDAC group (69.2%, 60.7% ) were significantly higher than that in the SDMSC group (50.8%, 42.1%) (p=0.025, 0.019). For patients in the intermediate risk group, the 3-year OS and EFS rates in the HDAC group (72.5%, 56.7% ) were higher than that in the SDMSC group (49.1%, 38.0%) (p=0.028, 0.093). This study indicates that for young adult AML patients, HDAC consolidation achieves a higher long-term survival than SDMSC, especially for patients in the intermediate-risk group according to the 2022 ELN risk stratification.